2019
DOI: 10.1364/ol.45.000001
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz tunable filter and modulator based on magneto plasmon in transverse magnetized InSb

Abstract: The transverse magneto-optical (MO) effect of InSb has been theoretically and experimentally investigated in the terahertz (THz) regime. The calculated photonic band structure and experimental measurements show that a unique circularly polarized magneto plasmon mode, and a linearly polarized transverse magnetic mode can be sensitively manipulated by a weak magnetic field. Moreover, these results indicate that transverse magnetized InSb can be used as a THz tunable high-pass filter and a MO modulator. The cutof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…We demonstrate that the resonant circuit can be tuned over a wide frequency range by adjusting any of the following: 2D electron density, the external perpendicular magnetic field, or the size of the contact electrodes. Due to their subwavelength confinement, the proposed 2D plasmonic structures can be used to design different 2D plasmonic devices and metamaterials [17][18][19][20][21][22][23][24][25][26][27][28][29][30].…”
mentioning
confidence: 99%
“…We demonstrate that the resonant circuit can be tuned over a wide frequency range by adjusting any of the following: 2D electron density, the external perpendicular magnetic field, or the size of the contact electrodes. Due to their subwavelength confinement, the proposed 2D plasmonic structures can be used to design different 2D plasmonic devices and metamaterials [17][18][19][20][21][22][23][24][25][26][27][28][29][30].…”
mentioning
confidence: 99%
“…2a illustrates the schematic diagram of the experimental setup. In the measurements, we used an electromagnet to generate a homogeneous magnetic field perpendicular to the device plane, and the poles of the electromagnet were fixed on two sides of the chip 20 , 21 . Moreover, a magnetometer was used to measure the strength of the field.…”
Section: Resultsmentioning
confidence: 99%
“…Schemes based on Faraday effect 14 , 17 and magneto-optical Kerr effect 15 are introduced to design isolators with the help of polarization-converting elements. High-mobility semiconductors (InSb 18 21 , HgTe 22 ), graphene 23 , 24 , ferrofluid 25 , and magnetic materials 14 are candidates that can be utilized to generate polarization rotation of terahertz waves. The other kind of method is based on the unidirectional absorption 26 , 27 and reflection 16 , 28 , which results from the nonreciprocal directional dichroism 26 , 27 , 29 31 and nonreciprocal reflection loss of the magnetic materials in specific directions 16 , 28 .…”
Section: Introductionmentioning
confidence: 99%
“…The transmission, polarization, and magnetooptical properties of InSb have been widely investigated in recent years. [31][32][33][34][35][36][37][38][39][40][41][42] For instance, in 2018, Lin et al [36] reported a nonreciprocal THz reflection on the InSb with the transverse magneto-optical effect (i.e., Voigt configuration). This one-way mirror achieves 35 dB isolation with 6.2 dB insertion loss for a certain linearly polarized (LP) state.…”
Section: Introductionmentioning
confidence: 99%
“…The transmission, polarization, and magneto‐optical properties of InSb have been widely investigated in recent years. [ 31–42 ] For instance, in 2018, Lin et al. [ 36 ] reported a nonreciprocal THz reflection on the InSb with the transverse magneto‐optical effect (i.e., Voigt configuration).…”
Section: Introductionmentioning
confidence: 99%